COMPUTERISED TOMOGRAPHIC SCANNING FOR HEADACHE: CT Scan for Headache - Raza, Brig Saleem; Syed, Tahir Mukhtar; Siddiqi, Hammad Ahmad (Pakistan Armed Forces Medical Journal, 2010)
Objective: To assess the utility of Computerized Tomographic (CT) scanning of brain in the evaluation of patients presenting with headache.Study Design: Cross-sectional retrospective study.Place and Duration of Study: Department of Radiology, Pakistan Air Force Hospital, Islamabad from April 2007 to August 2009.Patients and Methods: The referral forms of CT scanning of brain for evaluation of headache, available in our radiology department were reviewed. Patients were divided into two groups. Group I included those patients who’s only presenting complaint was headache while group II patients had other symptoms associated with headache. The results of their CT scans of brain were compiled and analyzed.Results: Out of a total of 829 CT scans of brain 58 were done for evaluation of headache. Twenty four (41%) patients had a CT scan for headache only (group I) and all of them had a normal CT of brain. Rest of the patients had headache with other associated symptoms (group II). Out of 34 (59%) of group II patients, four (12%) had an abnormality.Conclusion: CT scanning of brain is not useful in the diagnosis of headache in the absence of other associated symptoms and/or signs.